Análise do uso e ocupação do solo das margens de um reservatório e a sua influência na qualidade da água - Oliveira, Herison Alves de (2013)
The building of water reservoirs has become a solution for water scarcity of the semiarid regions, however, the land use and occupation near the margins of the reservoirs have been causing serious damage to water quality, harming their use. This paper aims to analyze the land use and occupation in the margins of the Northeast reservoir and evaluate their influence on the water quality, to identify the areas and activities that represent an higher risk of contamination to the reservoir. The study was conducted at the reservoir Dourado, located in the city of Currais Novos - RN, during the period from August 2012 to February 2013. Were defined six areas regarding the land use and occupation, then, Water samples were collected from the margins in these areas for the characterization of water quality. The results showed that almost all Permanent Preservation Areas (PPA) from the reservoir is degraded, increasing the susceptibility of large input of nutrients and contaminants loads. The water reservoir showed low quality, being with strong evidence of eutrophication due to the nutrient accumulation arising from the activities surrounding the reservoir, mainly from agriculture and Livestock. The Areas 1 and 2 are the areas that present a greater risk of reservoir degradation, because are the possible major sources of nutrients (phosphorus total, orthophosphate and nitrate), however, due to the small size of the reservoir, any compound that reaches its margins ultimately affects the water quality of the same